Teenage Pregnancy in Indonesia: Determinants and Outcomes - Rati Purnama Sari; Verra Widhi Astuti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
This review aims to identify determinants and outcomes associated with teenage pregnancy in Indonesia.  A search in PubMed, ScienceDirect, and google scholar databases in the last ten years (2011 to 2021) was conducted. The keywords were "teenage pregnancy" OR "adolescent pregnancy" AND "Indonesia". Journal criticism used CASP. Sixteen articles met the inclusion criteria. The most related determinants to teenage pregnancy were early marriage, economic status, educational level, knowledge, and access to information. Teenage pregnancies have a high risk of maternal and neonatal consequences such as anemia, preeclampsia, preterm birth, and low birth weight. Outcome problems of teenage pregnancy in Indonesia show a similar impact to the impacts revealed in studies in other countries. Women who have teenage pregnancies need support in getting access to adequate antenatal care to avoid the risk of complications for both mother and fetus. Effective education could be one of the efforts to raise the legal age of marriage. Collaboration of the stakeholders and policymakers is needed to prevent teenage pregnancy, especially in groups that tend to be at risk. Abstrak: Review ini bertujuan untuk mengidentifikasi determinan dan outcome yang berhubungan dengan kehamilan remaja di Indonesia. Dilakukan pencarian pada database PubMed, ScienceDirect, dan google scholar dalam sepuluh tahun terakhir (2011-2021). Kata kuci yang digunakan adalah “teenage pregnancy” OR “adolescent pregnancy” AND “Indonesia”. Pembahasan jurnal menggunakan CASP. Sebanyak 16 artikel memenuhi kriteria inklusi. Determinan yang paling terkait dengan kehamilan remaja adalah pernikahan dini, status ekonomi, level pendidikan, pengetahuan dan akses informasi. Kehamilan remaja berisiko tinggi terhadap maternal dan neonatal seperti anemia, preeclampsia, kelahiran premature, dan berat bayi lahir rendah. Permasalahan outcome dari kehamilan remaja di Indonesia menunjukkan dampak yang serupa dengan studi dari negara lainnya. Wanita yang menjalani kehamilan remaja membutuhkan dukungan untuk memperoleh akses antenatal care yang adekuat untuk mencegah risiko komplikasi pada ibu dan janin. Edukasi yang efektif bisa menjadi salah satu upaya meningkatkan usia pernikahan. Kolaborasi stakeholder dan pembuat pebijakan dibutuhkan untuk mencegah kehamilan remaja, khususunya pada kelompok berisiko.